Factors influencing the prevalence and death rate of COPD: a pan-database ecological study covering 201 countries and regions from 1990 to 2021Research in context - Zihui Wang; Wenhan Cao; Zhixuan You; Shaoqiang Li; Mingshan Xue; Haiyang Li; Junfeng Lin; Guannan Cai; Yuqi Chen; Zhiman Liang; Chengtao Zhou; Xiaofang Wu; et al. (EClinicalMedicine, 2025)
Summary: Background: Chronic obstructive pulmonary disease (COPD) is a common, heterogeneous disease and may be influenced by diverse factors. However, gaps remain in previous studies regarding the exploration of potential influencing factors. This study aims to investigate the wide range of potential factors influencing COPD based on a pan-database ecological analysis. Methods: We integrated data from 17 global databases (e.g., the Global Burden of Disease Study) which encompass social, environmental, and health data across various regions. Generalized linear regression was used to analyze the association of cumulative and instant exposures of factors with COPD and to rank their importance. Spearman analysis was used to assess the correlation of various factors with COPD. Heatmaps, scatter plots, and nonclassical multidimensional scaling (i.e., network graph) were employed to visualize the correlations. Findings: The study aggregated 77 social and environmental factors, 85 lifestyle and dietary factors, 25 physiological indicators, and 28 diseases. In the cumulative exposure analysis, tobacco consumption, atmospheric pollutants (e.g., ozone, CO, and organic matter aerosol), biomass cooking, and climatic conditions (e.g., vapor pressure, solar radiation, and temperature) were found to be associated with COPD prevalence. Additionally, tobacco consumption, social factors (e.g., hunger index, gender inequality index, and education year), and climatic conditions significantly impacted death rates. The results for cumulative exposures were consistent with those for instant exposures. Network graph analysis indicated a positive correlation between COPD and chronic kidney disease, other chronic respiratory diseases, gout, and stroke. Interpretation: Various factors (e.g., tobacco consumption, atmospheric pollution, biomass cooking, temperature, social factors, and comorbidities) significantly influence COPD. Comprehensive interventions are needed to reduce the disease burden of COPD. Funding: The Foundation of Guangzhou National Laboratory (SRPG22-018, SRPG22-016), State Key Laboratory of Respiratory Disease (SKLRD-OP-202402), Zhejiang medical health science and technology project (2025KY1245), Multi-Center Clinical Research Project of Guangzhou Medical University (GMUCR2025-02009), and Guangzhou Municipal Science and Technology Bureau (SL2024A04J00706).